Perancangan Sistem Informasi Penggajian Guru Menggunakan PHP dan MySql Pada SMK Tiara Bangsa Bekasi - Pita Palupi (LPPM STMIK AL MUSLIM, 2024)
The rapid development of technology and science, supported by quality and adequate human resources, is expected to be able to create a system that can help with daily activities, especially in the payroll process. The payroll data management system at Tiara Bangsa Vocational School in Bekasi still uses a manual number management application. The problems that arise are the occurrence of human error, files or data that are less secure and salary data management time that is less efficient. It is hoped that this research can speed up the process of managing payroll data from a manual system to a computerized system which will make work easier and manage teacher salaries quickly and on time. The method used is the Waterfall method which is able to create a system in stages. From the research conducted, it is hoped that the teacher payroll information system can be used and help manage teacher salary calculations and search for teacher data quickly and accurately.. Keywords: information system, payroll information system, waterfall, salary data management